Comparative Analysis Of Calculation Of Expedition Services Using Full Costing And Variable Costing Methods (Case Study at PT. Pulau Indah Maju Palembang) - Natasyah Aliyah Ramadina; Alwi Alwi; Frans Habrizons (UNIVED Press, 2024)
This research has purpose to know how the calculation of tariffs for public goods transportation services with the company method and compared with full costing and variable costing approaches at PT. Pulau Indah Maju Palembang. This research was conducted using a comparative descriptive analysis technique that compares 3 methods in calculating freight forwarding rates, namely the company method, the full costing method, and the variable costing method. The data collection method used to obtain data and information that supports and complements each other regarding the calculation of freight forwarding rates is an interview with the main director of PT. Pulau Indah Maju, Observations, and documentation. The results of the research are for colt diesel trucks, the company's method is more profitable than the full costing and variable costing approach, for the ankle truck the company's method is more profitable than the full costing and variable costing approach, and for tronton trucks, the variable costing approach is more profitable than the company's method and the full costing approach. From the data analysis that has been carried out, the following conclusions can be drawn: there is no significant difference in the steps for determining the rate of delivery of goods. The absence of such a difference lies in the basis for determining tariffs.